Borg's rating of perceived exertion scales: do the verbal anchors mean the same for different clinical groups? - Dawes, H; Barker, K; Cockburn, J; Roach, N; Scott, O; Wade, D (2005)
OBJECTIVE: To examine the interpretation of the verbal anchors used in the Borg rating of perceived exertion (RPE) scales in different clinical groups and a healthy control group. DESIGN: Prospective experimental study. SETTING: Rehabilitation center. PARTICIPANTS: Nineteen subjects with brain injury, 16 with chronic low back pain (CLBP), and 20 healthy controls. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Subjects used a visual analog scale (VAS) to rate their interpretation of the verbal anchors from the Borg RPE 6-20 and the newer 10-point category ratio scale. RESULTS: All groups placed the verbal anchors in the order that they occur on the scales. There were significant within-group differences ( P >.05) between VAS scores for 4 verbal anchors in the control group, 8 in the CLBP group, and 2 in the brain injury group. There was no significant difference in rating of each verbal anchor between the groups ( P >.05). CONCLUSIONS: All subjects rated the verbal anchors in the order they occur on the scales, but there was less agreement in rating of each verbal anchor among subjects in the brain injury group. Clinicians should consider the possibility of small discrepancies in the meaning of the verbal anchors to subjects, particularly those recovering from brain injury, when they evaluate exercise perceptions.